2012
DOI: 10.3109/00016489.2012.687457
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of contralateral residual hearing in unilateral cochlear implant users – long-term findings

Abstract: Group mean threshold values in the non-implanted ears remained stable over 3, 4, 5 and 6 years post-implantation, except for significant deterioration at 4.0 kHz of both unaided (4.2, 5.2, 9.0 and 8.2 dB, respectively) and aided thresholds (8.1, 4.6, 6.1 and 8.3 dB, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, this design was chosen because it enabled exclusion of progressive hearing loss as a confounding factor and inclusion of the outcome with a CI. Recent research has demonstrated stability of contralateral residual hearing up to 2,000 Hz over more than 6 years after implantation [Yehudai et al, 2012]. This means that hearing status 1 year after implantation can be considered a good estimate of pre-operative hearing abilities.…”
Section: Design Limitationsmentioning
confidence: 99%
“…Nevertheless, this design was chosen because it enabled exclusion of progressive hearing loss as a confounding factor and inclusion of the outcome with a CI. Recent research has demonstrated stability of contralateral residual hearing up to 2,000 Hz over more than 6 years after implantation [Yehudai et al, 2012]. This means that hearing status 1 year after implantation can be considered a good estimate of pre-operative hearing abilities.…”
Section: Design Limitationsmentioning
confidence: 99%
“…Не без оснований в последние годы возрос научный и потребительский интерес к одномоментной билатеральной кохлеарной имплантации у детей [9]. У глухих пациентов бинауральный слух может быть воссоздан двумя способами: посредством бимодальной стимуляции -использования кохлеарного импланта с одной стороны и слухового аппарата контралатерально, а также билатеральной кохлеарной имплантацией [10]. В свете последних научных исследований одностороннее слухопротезирование (один слуховой аппарат либо один кохлеарный имплант) представляется нецелесообразным ввиду развития сенсорной депривации слуховой зоны в коре головного мозга.…”
Section: Introductionunclassified
“…Moreover, bimodal hearing can offer the unique opportunity of combining complementary information by having access to two distinct modalities. Contralateral residual hearing is mainly situated in the low frequency region [12], which is known to contain cues regarding e.g. voice fundamental frequency, prosody and music [13-16].…”
Section: Introductionmentioning
confidence: 99%